Estudo Taxonômico das Espécies de Hypnaceae (Bryophyta) na Amazônia Brasileira. - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2006)
The family Hypnaceae Schimp. has, as the bryophytes in general, a great ecological importance, although the studies on these plants are still insufficient. This family is widely distributed in the Neotropics. It has 30-40 genera and about 1000 species described in the world literature. Of these, about 6 genera and 17 species are cited for the Amazon region. The objective of this work is to confirm the presence of these 17 species, as well as to investigate the possible occurrence of others and to carry out taxonomic studies. We analyzed 250 exsiccata of Hypnaceae Schimp. deposited in the MG herbarium from various regions: Belém, Amazonas, Oiapoque, Rondônia, Tucuruí, Barcarena, Serra dos Carajás, among others. The results found so far indicate the presence of 5 genera and 9 species in the MG Herbarium. It was observed that the species Chryso-hypnum diminutivum (Hampe) W. R. Buck and Ectropothecium leptochaeton (Schwagr.) W. R. Buck occur the most, 92 times and 48 times, respectively. Besides these two species, 7 other species were also analyzed, which presented a lower number of occurrences. Since there are still materials deposited in the herbariums of other Amazonian Institutions, such as those of INP A, IAN and others, to be studied, the conclusion is not definitive, but it is possible to advance that a greater emphasis on studies of Bryophytes is necessary to increase the knowledge of this group in the Brazilian Amazon.
Taxonomic Study of the Species of Hypnaceae (Bryophyta) in the Brazilian Amazon.
Keywords: Hypnaceae Schimp; Bryophyta; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::TAXONOMIA VEGETAL